Evaluasi Program Internet Publik di Kota Tanjungpinang dalam Mendukung Inklusi Digital - Fournely Aritasia Siahaan; Bismar Arianto; Ella Afnira (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to evaluate the implementation of the Public Internet Program in Tanjungpinang City in supporting digital inclusion. Based on the 2018-2023 Strategic Plan document from the target of 100 points, only 34 public wifi points were realized. The evaluation was carried out using the theory of William N Dunn (2003), using six indicators, namely, effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This research uses a qualitative approach with data collection techniques through observation, interviews, and documentation of 12 informants. The results of this study indicate that the implementation of the program has been running but not optimal. This can be seen in the effectiveness indicator where the placement of access points is less strategic, because it is located in upper-class housing which generally already has its own internet access, then the network quality is less stable with the bandwidth provided of 20 Mbps through a scramble system where the ideal standard according to the IT perspective is 2 Mbps per user outside watching YouTube. In the efficiency indicator, from 2013-2023 the realization did not reach the target set at the beginning, then the lack of maintenance resulted in 8 internet points not working. The adequacy indicator has not been said to be optimal in meeting needs through value, opportunity, and method adjustment as evidenced by the fact that there is no national standard as a reference in program implementation and unclear location data collection. In the equity indicator, there is a mismatch in infrastructure facilities, small areas have not been reached, and there is 1 location point that is locked. The responsiveness indicator is good, but there is still low participation from the community. Finally, the accuracy indicator is directed towards the community, but the implementation is not in accordance with the needs, and has not reached the initial target.